Kelimpahan dan Dominansi Lalat Buah (Diptera: Tephritidae) pada Pertanaman Cabai (Capsicum annuum L.), di Desa Paya Benua, Bangka - Saputra, Herry Marta; Sarinah, Sarinah; Hasanah, Mardian (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2019)
Fruit flies Bactrocera spp. (Diptera: Tephritidae) is one of the major pests in chili plants. The information about abundance and dominance of fruit fly species in chili orchard was limited, especially in Bangka Island. The purpose of this study was to determine the abundance and dominance species of fruit flies found in the chili orchard. This field experiment was conducted in the three chili orchard, Paya Benua Village, Bangka. This research used survey method by placing traps with methyl eugenol on host plants, in which four traps were being placed for each location. Traps were set in the morning (06.00-10.00), noon (10.00-14.00), and afternoon (14.00-18.00). The fruit fly species from trapping were identified as Bactrocera carambolae, Bactrocera dorsalis, and Bactrocera umbrosa. A total of 899 individuals were captured, with abundance of 251, 546, 102 individuals for Bactrocera carambolae, Bactrocera dorsalis, and Bactrocera umbrosa, respectively. The results showed that fruit fly Bactrocera dorsalis as the most abundant and dominant species in chili orchard, Paya Benua Village, Bangka.